Agronomic factors affecting dryland grain sorghum maturity and production in northeast Colorado - Sauer, Sally M., author; Johnson, Jerry J., advisor; Hansen, Neil C., committee member; Jha, Ajay K., committee member; McMaster, Gregory S., committee member; Vigil, Merle F., committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.